2006
DOI: 10.1097/00042737-200603000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing quality of outpatient care for patients with inflammatory bowel disease: the importance of specialist clinics

Abstract: By these criteria, the specialist IBD clinic provided better care than the non-specialist general gastroenterology clinics. Even in the specialist clinic, however, the care of a minority of patients did not fulfil certain criteria, emphasizing the need for a critical audit of outpatient management of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…This service utilizes the Brazilian government assistance program for patients with IBD, and consequently is able to provide free medical care, free laboratory tests and treatment with high cost drugs. These conditions have significantly improved the care delivered to IBD patients in this region, with good results as already observed by others (17,19) . The dates used in this study were based mainly on sequential register of cases of patients from a single general hospital, but limiting the results to cases coming from the investigated area.…”
Section: Resultssupporting
confidence: 68%
“…This service utilizes the Brazilian government assistance program for patients with IBD, and consequently is able to provide free medical care, free laboratory tests and treatment with high cost drugs. These conditions have significantly improved the care delivered to IBD patients in this region, with good results as already observed by others (17,19) . The dates used in this study were based mainly on sequential register of cases of patients from a single general hospital, but limiting the results to cases coming from the investigated area.…”
Section: Resultssupporting
confidence: 68%
“…In this context, it has been suggested that centres with specialist IBD out-patient clinics whose only interest is IBD management are the optimal model for IBD care and that as a consequence adherence may be better in patients attending them. 8,57 CONCLUSIONS Non-adherence to thiopurines in IBD patients is more common in young adults than adults. The reasons for this remain unclear: whether they relate to differences in IBD knowledge, doctor/patient discordance or attitudes towards maintenance medication between young adults and adult needs further study.…”
Section: External Validitymentioning
confidence: 99%
“…Furthermore, given this strong increase, IBD units are clearly necessary to provide IBD patients with optimum care, as they often require a personalized strategy with therapies requiring more stringent control measures than usual (3,4). Also, multidisciplinary teams are needed to provide appropriate care of the wide range of symptoms of this disease (5).…”
Section: Introductionmentioning
confidence: 99%